Estimation the intensity of germ-grain models with overlapping grains - Ghorbani, Hamid (Image analysis and stereology, 2003)
Formulas are derived for the spherical contact distribution of a planar germ-grain model Z with circular grains where the germs form either a "segmentcluster" process or a "line-based" Poisson point process. They are used in order to estimate the intensity lambda of the germ process by means ofthe spherical contact distribution function. As an application the number ofdislocations on a silicon wafer is estimated.
Keywords: Delec, velikost; Particle Size; Silicij; Silicon; Skupek, analiza; Cluster Analysis; Verjetnost; Probability; Poissonov proces; delci; krogle; dislokacije; modeli